Leadership crisis in African higher education in the 4IR: lesson(s) for the future - Chinaza Uleanya (Cogent Education)
African higher education has experienced different challenges in the past decade with regard to embracing and incorporating the practices of the Fourth Industrial Revolution. This has led to conferences, summits, and special journal issues, among others, exploring the submissions of scholars from different perspectives. Therefore, this study explores scholarly views from the perspective of the leadership crisis in African institutions of learning in the Fourth Industrial Revolution (4IR) era. This systematic review was conducted through the use of bibliometric analysis. Following a search on Web of Science and scrutiny, 7,258 articles were retrieved and analyzed using RStudio software. The findings of the study show that leadership in African institutions of learning experience crises due to constraints in professional development, finance, infrastructure, and curricula, among others. Thus, this article argues that it is possible for irrelevant education to be provided, whereas education for relevance is to be pursued. Hence, there are lessons to be learnt by leaders of African higher institutions to ensure sustainability, future progress and education for relevance. For instance, amongst others, redesigning of the curricula as well as upskilling are pivotal for relevance in the 4IR era.